So what? Transition management as a transformative approach to support governance capacities in cities. - Hölscher, Katharina (Springer, 2018)
This chapter synthesises the insights from the various book contributions to critically reflect on what transition management offers when applied in and for cities. In this book, transition management has been suggested as a transformative governance approach in and for cities. Transition management seeks to provide impulses for systemic change by creating spaces for developing innovative ideas and practices and for empowering actors to develop transition experiments. It also holds the potential to fundamentally challenge existing planning and governance systems by aligning a diversity of actors, networks and initiatives under a shared and long-term sustainability vision and questioning existing roles and responsibilities of actors. We explore how transition management thus contributes to building transformative capacity for systemic change and orchestrating capacity for the coordination of self-organisation. On the basis of the book contributions we discuss the potentials, opportunities and challenges of transition management as a prescriptive and transformative governance approach. We conclude by identifying implications for transition management in light of the objective to strengthen governance capacities for navigating sustainability transitions in cities.
Keywords: Nachhaltige Stadtentwicklung; Akteur; Transformation; Wissenstransfer; Implementation; Innovation; Städtevergleich